Strangers in the university: Unforeseen students in Portuguese higher education - Justino, E.; Dias, D.; Santos, G. (2018 CHER International Higher Education Conference, 2018)
In Portugal, the higher education democratization should not be restricted to an analysis of the mass phenomenon, looking only at the number of young people in the age group within education processes. Indeed, it appears that in recent decades, with higher incidence since the 80s and throughout the 90s, the number of students in higher education has grown very considerably. This increase is largely explained by investments made on the expansion of the network, provided by the public authorities (leveraged by structural funds), and by the private sector (mostly supported by the tuition fees). In 1974, the Portuguese higher education was an elitist system, with a very low participation rate (around 7%) whilst most of its enrolled students came from more resourceful families (Dias, 2015). Nowadays higher education holds students from a lower social and cultural status which had no representation 30 or 40 years ago (Neave, 2011). However, the following issues remain unanswered: why families with a greater social, cultural and economic capital are over represented in Portuguese higher education compared to its representative weight in the Portuguese society? Is this a real assumption, considering the context of each Portuguese Higher Education Institution (HEI) at a regional level? The issue of democratization will not be fully understood if we do not consider the less visible phenomena, the constraints of social and economic order that determine different objective choices and consequent frequency of a higher education program. We cannot perceive higher education democratization process, without regarding to the schooling strategies of different social classes, and the correlation between those strategies in function of the existing resources, and regarding expectations of ascendant social mobility. Access to certain cultural or educational goods, the economic capacity to invest in children's education, or the perception that families must invest in a learning journey from the early years it’s largely dependable on the family's social background (Amado-Tavares, 2008).